Ventilation Strategies During Extracorporeal Membrane Oxygenation for Neonatal Respiratory Failure: Current Approaches Among Level IV Neonatal ICUs. (15th November 2022) - Ibrahim, John; Mahmood, Burhan; DiGeronimo, Robert; Rintoul, Natalie E.; Hamrick, Shannon E.; Chapman, Rachel; Keene, Sarah; Seabrook, Ruth B.; Billimoria, Zeenia; Rao, Rakesh; Daniel, John; Cleary, John; et al.
Abstract : OBJECTIVES: To describe ventilation strategies used during extracorporeal membrane oxygenation (ECMO) for neonatal respiratory failure among level IV neonatal ICUs (NICUs). DESIGN: Cross-sectional electronic survey. SETTING: Email-based Research Electronic Data Capture survey. PATIENTS: Neonates undergoing ECMO for respiratory failure at level IV NICUs. INTERVENTIONS: A 40-question survey was sent to site sponsors of regional referral neonatal ECMO centers participating in the Children's Hospitals Neonatal Consortium. Reminder emails were sent at 2- and 4-week intervals. MEASUREMENTS AND MAIN RESULTS: Twenty ECMO centers responded to the survey. Most primarily use venoarterial ECMO (65%); this percentage is higher (90%) for congenital diaphragmatic hernia. Sixty-five percent reported following protocol-based guidelines, with neonatologists primarily responsible for ventilator management (80%). The primary mode of ventilation was pressure control (90%), with synchronized intermittent mechanical ventilation (SIMV) comprising 80%. Common settings included peak inspiratory pressure (PIP) of 16–20 cm H2 O (55%), positive end-expiratory pressure (PEEP) of 9–10 cm H2 O (40%), I-time 0.5 seconds (55%), rate of 10–15 (60%), and Fio 2 22–30% (65%). A minority of sites use high-frequency ventilation (HFV) as the primary mode (5%). During ECMO, 55% of sites target some degree of lung aeration to avoid complete atelectasis. Fifty-five percent discontinue inhaled nitric oxide (iNO) during ECMO, while 60% use iNO when trialing off ECMO. Nonventilator practices to facilitate decannulation include bronchoscopy (50%), exogenous surfactant (25%), and noninhaled pulmonary vasodilators (50%). Common ventilator thresholds for decannulation include PEEP of 6–7 (45%), PIP of 21–25 (55%), and tidal volume 5–5.9 mL/kg (50%). CONCLUSIONS: The majority of level IV NICUs follow internal protocols for ventilator management during neonatal respiratory ECMO, and neonatologists primarily direct management in the NICU. While most centers use pressure-controlled SIMV, there is considerable variability in the range of settings used, with few centers using HFV primarily. Future studies should focus on identifying respiratory management practices that improve outcomes for neonatal ECMO patients.